Intracellular distribution of mammalian protein kinase a catalytic subunit altered by conserved Asn2 deamidation - Pepperkok, Rainer; Hotz-Wagenblatt, Agnes; Bossemeyer, Dirk; Kinzel, Volker (The journal of cell biology, 2000)
The catalytic (C) subunit of protein kinase A functions both in the cytoplasm and the nucleus. A major charge variant representing about one third of the enzyme in striated muscle results from deamidation in vivo of the Asn2 residue at the conserved NH2-terminal sequence myrGly-Asn-Ala (Jedrzejewski, P.T., A. Girod, A. Tholey, N. König, S. Thullner, V. Kinzel, and D. Bossemeyer. 1998. Protein Sci. 7:457-469). Because of the increase of electronegativity by generation of Asp2, it is reminiscent of a myristoyl-electrostatic switch. To compare the intracellular distribution of the enzymes, both forms of porcine or bovine heart enzyme were microinjected into the cytoplasm of mouse NIH 3T3 cells after conjugation with fluorescein, rhodamine, or in unlabeled form. The nuclear/cytoplasmic fluorescence ratio (N/C) was analyzed in the presence of cAMP (in the case of unlabeled enzyme by antibodies). Under all circumstances, the N/C ratio obtained with the encoded Asn2 form was significantly higher than that with the deamidated, Asp2 form; i.e., the Asn2 form reached a larger nuclear concentration than the Asp2 form. Comparable data were obtained with a human cell line. The differential intracellular distribution of both enzyme forms is also reflected by functional data. It correlates with the degree of phosphorylation of the key serine in CREB family transcription factors in the nucleus. Microinjection of myristoylated recombinant bovine Cα and the Asn2 deletion mutant of it yielded N/C ratios in the same range as encoded native enzymes. Thus, Asn2 seems to serve as a potential site for modulating electronegativity. The data indicate that the NH2-terminal domain of the PKA C-subunit contributes to the intracellular distribution of free enzyme, which can be altered by site-specific in vivo deamidation. The model character for other signaling proteins starting with myrGly-Asn is discussed.